La pratique des langues indigènes chez les franciscains de la Nouvelle-Espagne au XVIe siècle (province du Santo Evangelio de Mexico, 1570) - Eric Roulet (Caravelle)
In New Spain the Franciscans realize very soon that if they want to convert the Indian masses, they must have a common language. Therefore, they learn the native tongues in order to practice their ministry. The Mexican councils of 1555 and 1556 turn this into a main goal. Quite a few clerics in charge of Indians can speak a native tongue by 1570. Nevertheless, their register in that language is very varied and, they don’t always know the language of the population they are dealing with : a fact which explains the permanence of translators. The evaluation of the number of speakers enables to determine more accurately the conditions and the impact of evangelization.